PENULISAN SKENARIO BERGENRE FIKSI ILMIAH MENGANGKAT KEUNIKAN KARTOGRAFI KOTA DENGAN PENDEKATAN RISET SEJARAH ‘ATMODIRONO’ - Adji, Titus Soepono (Acintya, 2016)
Atmodirono is experimentation screenwriting science fiction genre with the approach of historiography and science of cartography or mapping the city of Semarang. Historiography raised is related to the history of the city of Semarang from its inception to the present. In terms of cartography, this filmfocuses on the potential uniqueness map of Semarang who have axes secret that connects several points in the city of Semarang and other points in the world. Experimentation methods of mapping using the online application Google Earth Remote Sensing.Meanwhile, as the binder story, based onthe life story Atmodirono, an architect first Natives in the Dutch East Indies, where life is still rarely discussed and mysterious. Scriptwriting method used is the method of Richard Krevolin, who can work to work on the screenplay adaptation of the various processes that allow, in this case the historyof the city. Atmodirono figures and the map of Semarang. This story can end up being a critique of urban development is not organized at this time.Keywords: Science Fiction, Cartography, Atmodirono figures.